A simulation-based empirical study on the role of aviation logistics in driving high-quality and sustainable regional economic development: Focusing on dynamic mechanisms and key factors - Lijun Liang; Peirong Chen (PLoS ONE, 2025)
This study incorporates aviation logistics equipment into the analysis, considering current policy trends and development hotspots. By exploring the intricate relationship between aviation logistics and the regional economy, a System Dynamics model is created to identify the dynamic mechanisms and key factors that drive high-quality and sustainable regional economic development through aviation logistics. The primary objective is to establish a framework for resource allocation and policy adjustments tailored to regional needs. To validate the proposed framework, an empirical analysis of Sichuan Province is conducted. The findings indicate that: (1) Aviation logistics significantly contributes to regional economic development; (2) Aviation logistics equipment, a crucial component of the aviation logistics supply subsystem, demonstrates notable stability compared to demand and plays a pivotal role in fostering regional economic development; (3) Aviation logistics equipment software, in contrast to hardware, has a more pronounced impact on regional economic development and structural optimization. This study offers both theoretical and practical contributions: Firstly, it integrates aviation logistics equipment into the complex system framework, addressing a gap in the literature by defining and categorizing its role within the framework. Secondly, the dynamic model developed provides theoretical support for regional management and policy-making, facilitating improved resource allocation and policy optimization for high-quality and sustainable regional economic development. Finally, the study presents practical policy recommendations, making it highly valuable in practice based on the Sichuan case.